The Determinants of Wine Prices: A Systematic Literature Review - Gál, Péter (Competitio, 2020)
Wine is a highly differentiated product sold at a wide range of different prices. This article aims to provide a systematic review of the literature written on the determinants of wine prices globally. The article runs a search on the combination of keywords “wine”, “price”, “determinant” in the Web of Science, Scopus, JSTOR, ProQuest, and Science Direct databases. Based on a final set of 46 articles written between 1998 and 2018, results suggest that terroir and quality ratings are the most significant determinants of wine prices, while objective quality and label data also determines wine prices, though to a different extent and with a different sign in some cases. The hedonic pricing method was the most common way of analyzing the relationship between wines prices and their determinants, and results are similar for most regions and varieties. We believe that our results can be useful for researchers, stakeholders, and even for decision-makers in better understanding the factors lying behind wine prices.Journal of Economic Literature (JEL) codes: D12, D40 Q11